(:unas) unassigned - KENNY, EAMONN (My University, 2000)
The increase in mobile communications traffic has led to heightened interest in the use of deterministic propagation methods together with digital building and terrain databases for propagation prediction in urban areas. Ray methods have been particularly popular, and there are many papers in the literature describing the performance of various approaches to ray tracing. This paper describes a powerful three-dimensional (3-D) software suite for urban propagation modeling which, although based on 3-D ray tracing (using images), draws upon an ensemble of propagation tools including physical optics using the fast far-field approximation, the parabolic equation approximation for propagation over multiple buildings, and uniform theory of diffraction (UTD). Many ray-tracing methods determine ray paths between the transmitter and a single arbitrary receiver This paper adopts an approach of a transmitter to a multiple receiver technique, resulting in greatly reduced computational times. The associated method can handle both indoor and outdoor propagation on both flat and undulating terrain. Terrain is represented as a set of triangular two-dimensional (2-D) patches, while buildings and clutter are represented using layers of polygons
PUBLISHED
Keywords: Propagation; Electromagnetics; Ray-tracing; Microcellular; Telecommunications